Tracing the history and biogeography of the Australian blindsnake radiation. (23rd November 2012) - Marin, Julie; Donnellan, Stephen C.; Blair Hedges, S.; Doughty, Paul; Hutchinson, Mark N.; Cruaud, Corinne; Vidal, Nicolas; Masters, Judith
Abstract Aim We investigated the biogeographical history of Australian blindsnakes (Ramphotyphlops) with reference to Australia's palaeoclimatic history over the past 20 Myr, particularly the development of an extensive arid zone over this period. Terrestrial vertebrate lineages dating back to the Miocene or earlier are predicted to display some or all of the following patterns: (1) for taxa including mesic, arid and monsoonal representatives, a mesic distribution should be phylogenetically ancestral; (2) mesic and monsoon tropical lineages should have diverged before the onset of aridification (with arid lineages appearing later); and (3) refuges may have allowed local persistence and diversification of lineages in the monsoon tropical and mesic zones since the mid‐Miocene. Location Continental Australia. Methods We compiled a molecular data set comprising one mitochondrial and three nuclear genes for 107 individuals belonging to 28 blindsnake species. Phylogenetic relationships were reconstructed using maximum likelihood and Bayesian inference with RAxML and MrBayes, respectively. Divergence times were assessed using multidivtime. Ancestral habitat states (arid and non arid) were reconstructed using the maximum likelihood method implemented in Mesquite. Results The age of the Australian Ramphotyphlops radiation was estimated at 21.9 Ma (95% credibility interval: 30.2–15.1 Ma). Mesic and monsoon tropical lineages are older than the onset of aridification, with mesic distribution appearing as ancestral on phylogenies. After the onset of aridification, lineages persisted and diversified in mesic, tropical and/or rocky refugia. Arid lineages diversified more recently (< 5 Ma). Main conclusions Australian blindsnakes join several other Australian squamate lineages with tropical‐mesic origins that successfully adapted to the expansion of aridity since the mid‐Miocene (c. 17 Ma) and now show evidence of multiple relatively recent evolutionary radiations across Australia. We further demonstrate that localized refugia permitted persistence and diversification of mesic taxa, with arid lineages diversifying much later (< 5 Ma) when the arid zone was well established.